Addressing weak inflation: The European Central Bank's shopping list - Zsolt Darvas; Grégory Claeys; Silvia Merler; Guntram B. Wolff (Bruegel, 2014)
Euro-area inflation has been below 1 percent since October 2013, and medium-term inflation expectations are well below 2 percent. Forecasts of the return to target inflation have proved wrong. The European Central Bank should act forcefully, but should undermine neither the major relative price adjustments between the euro-area core and the periphery that are needed, nor the ongoing process of addressing weaknesses in Europe's banking system. Reducing the deposit rate or introducing another long-term refinancing operation could be beneficial, but would be unlikely to change substantially inflation expectations. Government bond purchases would be significantly beneficial, but in a monetary union with 18 different treasuries, such purchases are difficult for economic, political and legal reasons. We recommend a monthly asset-purchase programme of exteuro35 billion with a review of the amount after three months. EFSF/ESM/EU/EIB bonds, corporate bonds and assetbacked securities should be purchased, of which at least exteuro490 billion, exteuro900 billion and exteuro330 billion respectively are suitables. Bonds of sound banks could be considered after the completion of the ECB's assessment of bank balance sheets. While bond purchases distort incentives and make the ECB subject to private and public sector pressure, with potential consequences for inflation, such risks need to be weighed against the risk of persistently low inflation.
Keywords: 330